2021
DOI: 10.1371/journal.pone.0258030
|View full text |Cite
|
Sign up to set email alerts
|

Burden of invasive group B Streptococcus disease in non-pregnant adults: A systematic review and meta-analysis

Abstract: Background Streptococcus agalactiae or group B Streptococcus (GBS) has emerged as an important cause of invasive disease in adults, particularly among the elderly and those with underlying comorbidities. Traditionally, it was recognised as an opportunistic pathogen colonising and causing disease in pregnant women, neonates, and young infants. Reasons for the upsurge of invasive GBS (iGBS) among the elderly remain unclear, although it has been related to risk factors such as underlying chronic diseases, immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…As an opportunistic pathogen, GBS (or Streptococcus agalactiae ) asymptomatically resides in the gastrointestinal and/or female genital tract of 25-30% of healthy adults (Wilkinson, 1978, Regan et al ., 1991) but can cause severe infections in some individuals, such as pregnant people and newborns, the elderly, and patients living with cancer or diabetes (Nandyal, 2008, Pimentel et al ., 2016, Russell et al ., 2017, Patras & Nizet, 2018, van Kassel et al ., 2019, Navarro-Torne et al ., 2021). Within the female genital tract, GBS coexists and/or competes with the vaginal microbiota and, therefore, has evolved mechanisms to survive these encounters while also avoiding immune clearance (Okumura & Nizet, 2014, Vrbanac et al ., 2018, Coleman et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As an opportunistic pathogen, GBS (or Streptococcus agalactiae ) asymptomatically resides in the gastrointestinal and/or female genital tract of 25-30% of healthy adults (Wilkinson, 1978, Regan et al ., 1991) but can cause severe infections in some individuals, such as pregnant people and newborns, the elderly, and patients living with cancer or diabetes (Nandyal, 2008, Pimentel et al ., 2016, Russell et al ., 2017, Patras & Nizet, 2018, van Kassel et al ., 2019, Navarro-Torne et al ., 2021). Within the female genital tract, GBS coexists and/or competes with the vaginal microbiota and, therefore, has evolved mechanisms to survive these encounters while also avoiding immune clearance (Okumura & Nizet, 2014, Vrbanac et al ., 2018, Coleman et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A 12-year retrospective study from 2004 to 2015 obtained from two hospitals in Bangkok, Thailand, revealed that invasive GBS infections were higher among the elderly and middle-aged adults compared to neonates ( Figure S1 ). This reflects a potential health threat to older adults from GBS invasive disease [ 40 ]. There are five major CCs of human GBS circulating around the globe; CC1, CC10, CC17, CC19, and CC23 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in some cases, it can present with bacteraemia in non-pregnant adults. Retrospective studies [ 2 , 3 ] and a recent meta-analysis [ 10 ] studied some factors predisposing to develop S. agalactiae infections and bacteraemia in non-pregnant adults, namely diabetes, malignancies, liver and renal disease and immunosuppressive disorders.…”
Section: Discussionmentioning
confidence: 99%